DEVELOPMENT POTENTIAL OF SMALL AND MEDIUM ENTERPRISES BASED ON SPATIAL CONCENTRATION IN SARBAGITA AREA - Lumbantobing, Agape; Munibah, Khursatul; Agung Adrianto, Hari (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
Several studies have found that disparities still exist between regions within the Sarbagita area. As a driving force for the regional economy, the role of Small and Medium Enterprises (SMEs) is important to be developed based on their potential in solving these problems. This study aimed to identify the potential of each type of SME based on aspects of specialisation and spatial concentration using the Krugman Index, Hoover Ballasa Index, and LISA analysis methods. The data used in this study is based on the number of SME units in each area of the Sarbagita Area which are grouped based on eight categories of SME types. The research found that the specialisation categories of SME types from highest to lowest, namely: iron and steel; non-metallic mineral; wood goods; textile and apparel; printing and publishing; basic chemical; fertilizers, and plastic equipment, metal goods; food and beverage. The results of this study also show that there are concentrations and spatial relationship patterns of each type of SME with High-High (H-H), High-Low (H-L), Low-High (L-H), and Low-Low (L-L) patterns. This spatial information is expected to be a reference for directing SME development strategies in the Sarbagita area. Keywords: small and medium industry; spatial concentration; Sarbagita area